Black bear ecology and human-bear interactions in an urban system - Baruch-Mordo, Sharon, author; Wilson, Kenneth R., advisor; Breck, Stewart W., advisor; Webb, Colleen T., committee member; Crooks, Kevin R., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: urban ecology; human-bear conflict; American black bear; Ursus americanus